Exploring Job Satisfaction and Intention to Leave Among Athletic Trainers Working With Tactical Athletes in Military Clinical Practice Settings - Kristen C. Schellhase; Weston Adam; Ananda Layne; Marielle Ulan; L. Colby Mangum (International Journal of Athletic Therapy and Training, 2026)
Military clinical practice settings have undergone rapid growth in recent years, and the literature suggests that these emerging clinical practice settings have better job satisfaction. This study explored job satisfaction and intention to leave among 25 athletic trainers working with tactical athletes in the military clinical practice setting and found that they are satisfied with their jobs and have low intention to leave. They are especially satisfied with their nature of work and their coworkers. They are satisfied with their salary but are dissatisfied with the lack of opportunities for promotion and raises. Employer policies that create clear advancement opportunities and opportunities for raises could enhance job satisfaction further.